KAJIAN AGRONOMI KORO PEDANG (Carnavalia ensiformis L.) PADA JARAK TANAM DAN KOMPOSISI PUPUK CAMPURAN NPK DI LAHAN PASIR - Darnawi Darnawi (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
The study was conducted determines the effect of plant spacing and the provision of NPK fertilizer composition mixture on the growth and yield of koro sword (Carnavalia ensiformis L.) dilahan pasir.Percobaan conducted in farmer's land in Depok, Parangtritis from July to December 2013. This research was arranged as factorial with complete randomized block design (RAKL) is repeated three times. The first factor is a spacing (A) which consists of three levels, namely: a distance of 40 cm x 80 cm (J1), a distance of 50 cm x 80 cm (J2), a distance of 60 cm x 80 cm (J3). The second factor is the composition of NPK fertilizer mixture that consists of four levels, namely: the ratio of 1: 1: 1 (25:25:25) (P1), a ratio of 1: 2: 2 (25:50:50) (P2), the ratio of 2 : 2: 2 (50:50:50) (P3), a ratio of 2: 3: 3 (50:75:75) (P4). The variables measured were plant height was six months old, weighs fresh stover age of six months, the weight of dry stover age of six months, dry seed weight per plant, grain weight dry weight of 100 seeds and dry beans per hectare. The analysis showed no effect of the interaction between plant spacing and composition of NPK fertilizer mixture, as well as the treatment plant spacing and composition of themix NPK fertilizer did not significantly affect all the variables observed.